2023
DOI: 10.1161/circresaha.122.321926
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-Redox Control of Mac-1 De-Adhesion by PDI Promotes Directional Movement Under Flow

Abstract: BACKGROUND: Neutrophil migration is critical to the initiation and resolution of inflammation. Macrophage-1 antigen (Mac-1; CD11b/CD18, αMβ2) is a leukocyte integrin essential for firm adhesion to endothelial ICAM-1 (intercellular adhesion molecule 1) and migration of neutrophils in the shear forces of the circulation. PDI (protein disulfide isomerase) has been reported to influence neutrophil adhesion and migration. We aimed to elucidate the molecular mechanism of PDI control of Mac-1 affinity for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…Association of PDI with the α M chain, but not cleavage, lead to significant upstream migration when compared to unbound control, similar to the antibody blocking studies designed by Buffone et al (Buffone et al, 2019). In both studies (Buffone et al, 2019;Dupuy et al, 2023), globally blocking Mac-1 with oxidized PDI or monoclonal antibodies, lead to over 65% of cells crawling upstream. Dupuy and coworkers' result indicates that the engagement of PDI alone can promote upstream migration in neutrophils.…”
Section: Upstream Migration Observed In Other Cell Typessupporting
confidence: 63%
See 1 more Smart Citation
“…Association of PDI with the α M chain, but not cleavage, lead to significant upstream migration when compared to unbound control, similar to the antibody blocking studies designed by Buffone et al (Buffone et al, 2019). In both studies (Buffone et al, 2019;Dupuy et al, 2023), globally blocking Mac-1 with oxidized PDI or monoclonal antibodies, lead to over 65% of cells crawling upstream. Dupuy and coworkers' result indicates that the engagement of PDI alone can promote upstream migration in neutrophils.…”
Section: Upstream Migration Observed In Other Cell Typessupporting
confidence: 63%
“…We believe the difference between our results and the results from the Theodoly laboratory is due to differences in ICAM-1 density; we used lower densities of ICAM-1 which seems to have enhanced the mobility of neutrophils (Valignat et al, 2013;Buffone et al, 2019) A recent paper by Dupuy et al expanded upon the interplay between Mac-1 and LFA-1 in coordinating neutrophil upstream migration (Dupuy et al, 2023). By treating neutrophils with Protein disulfide Isomerase (PDI), Dupuy et al demonstrated that PDI localizes specifically to Mac-1 at the trailing edge of the cell and selectively cleaves disulfide bonds, leading to Mac-1 release of ICAM-1.…”
Section: Upstream Migration Observed In Other Cell Typesmentioning
confidence: 70%
“…In support of our hypothesis, the roles of extracellular thiol isomerase in the regulation of Mac-1 activity were previously documented, though with discrepancies. 27,28 Using gene conditional knockout mice, Hahm et al 27 showed that PDI increases the binding affinity of Mac-1 by regulating thiol exchange in CD11b and the clustering of Mac-1 without affecting its conformation. A more recent study showed that PDI cleaves the C224-C264 bond of CD18 to induce mechanical stress in the βI domain, which allosterically alters the exposure of the αI domain and decreases the binding affinity of Mac-1.…”
Section: Discussionmentioning
confidence: 99%
“…27 A more recent study showed that cleavage of a disulfide bond in the βI domain by extracellular PDI selectively regulates the disengagement of Mac-1 with ICAM-1 under shear. 28 In addition to PDI, ERp72 (endoplasmic reticulum–resident protein 72) was also reported on the surface of neutrophils and implicated in neutrophil activation. 29 It was reported that a polyclonal antibody against ERp72 suppressed neutrophil adhesion on activated endothelial cells.…”
mentioning
confidence: 99%
“…Endothelial inflammation (thromboinflammation) involves the upregulation of adhesion molecules including E-selectin, P-selectin, and intracellular adhesion molecule-1 (ICAM-1) [84], which are critical in the development of thrombotic diseases including stroke and cardiovascular events. Neutrophils are attracted to damaged endothelium, attach via integrins such as Mac-1 [85], and stimulate further inflammation, the formation of neutrophil-platelet aggregates and promote atherosclerosis [86]. NETs stimulate endothelial inflammation through the activity of NETs components such as cathepsin G [87].…”
Section: Mechanisms Of Neutrophil Activationmentioning
confidence: 99%